Optimizing Digital Marketing Through TikTok - Noviani, Lona; Nabella, Ratih Intania (Universitas Banten Jaya, 2024)
This research was conceived as a response to the rapid development of technology and the increase in internet users, particularly in Indonesia. With APJII surveys showing significant growth in internet users, particularly among Generation Z students, and Good Stats' prediction that active social media users will continue to increase, this research focuses on the role of social media as a business platform, particularly TikTok. This research highlights TikTok's great potential as a profitable digital marketing platform, especially by optimising the features provided. The method used in this research is a descriptive method with a qualitative approach. The data used is secondary data collected through literature study. The results of this study show that TikTok, a short video-based app, has gained great popularity in Indonesia. Data recorded that Indonesia is the second country with the most TikTok users in the world. The significant increase in TikTok users, including features such as For You Page (FYP), hashtag usage, TikTok Shop, and Live Shopping, shows great potential as a digital marketing tool. TikTok Shop, as the newest feature, provides an integrated e-commerce space in the app, while Live Shopping enables direct interaction between brands and audiences, enhancing the purchase experience. Collaboration with TikTok creators is also useful as an effective strategy in building trust and reaching a wider marketing target.